Epidemiological Assessment of Chlamydiasis among Women in Jalingo and Kurmi Local Government Areas, Taraba State, Nigeria - Mafe, Alice Njolke; Akwa, Vera Yafeh; Houmsou, Roberts Soumay (Darul Yasin Al Sys, 2025)
Bacterial sexually transmitted infections remain a major public health concern among adults globally. This study investigates the prevalence and associated risk factors of Chlamydia trachomatis infection among women in Jalingo and Kurmi Local Government Areas of Taraba State, Nigeria. Employing a cross-sectional design, 370 women aged 18–55 years were recruited from selected hospitals and clinics. Data collection involved structured questionnaires and laboratory analysis of endocervical swab samples using direct immunofluorescent assay (IFA) and polymerase chain reaction (PCR) for confirmation. The overall prevalence of C. trachomatis infection was 21.8%, with a higher rate in Jalingo (25.5%) compared to Kurmi (18.0%). The highest prevalence was recorded among women aged 18–24 years and those reporting multiple sexual partners. Other statistically significant risk factors included low educational attainment, inconsistent condom use, and a prior history of sexually transmitted infections. The findings underscore the necessity of integrating sensitive diagnostic methods, such as PCR, into routine STI screening to improve early detection and treatment outcomes. The study further emphasizes the need for targeted public health interventions, including routine chlamydia screening, comprehensive sexual health education, and improved access to sexual and reproductive health services in the region.